Synthesis and enhanced photocatalytic performance of graphene-Bi2WO6 composite - Gao, Erping; Wang, Wenzhong; Shang, Meng; Xu, Jiehui (Physical chemistry chemical physics : PCCP, 2011)
Graphene possesses excellent conductivity, adsorptivity, and controllability. The combination of photocatalysts and graphene will introduce these properties of graphene into photocatalysis. In this paper, graphene oxide-Bi 2 WO 6 composite was firstly prepared via in situ hydrothermal reaction in the presence of graphene oxide, then the graphene oxide was reduced by ethylene glycol and the graphene-Bi 2 WO 6 (G-BWO) composite was formed. The as-prepared graphene-Bi 2 WO 6 photocatalyst shows enhanced photocatalytic activity for the degradation of rhodamine B (RhB) under visible light (λ > 420 nm). The electronic interaction and charge equilibration between graphene and Bi 2 WO 6 lead to the shift of the Fermi level and decrease the conduction band potential, which has an important influence on the photocatalytic process. The enhanced photocatalytic activity could be attributed to the negative shift in the Fermi level of G-BWO and the high migration efficiency of photoinduced electrons, which may suppress the charge recombination effectively. By introducing graphene into photocatalysis, enormous enhancement of photocatalytic efficiency was achieved over graphene-Bi 2 WO 6 photocatalyst.